Utilization of Bamboo Sawdust as Oyster Mushrooms grown Media - Saaidin, Muhamad Syazwan; Masrol, Shaiful Rizal; Suloh, Noorsaiful Amri (Progress in Engineering Application and Technology, 2023)
The rapid increase in the Pleurotus ostreatus (oyster mushroom) growing industry in Malaysia requires the supply of suitable alternative materials as growing media other than rubber wood sawdust (RS). Thus, this study is conducted to observe the potential of bamboo sawdust (BS) from Betong (Dendrocalamus asper) variety as an alternative substrate for the cultivation of oyster mushroom which currently uses sawdust from the rubber trees. The grown media has been produced with 25%, 50% and 75% sawdust composition between BS and RS. Substrate with 100% BS and 100% RS were produced as control samples for comparison. The mushroom kit packaging for BS media-based substrates is successfully developed in this study. All substrate compositions were produced with addition of 10% bran and 1% agricultural lime. In the oyster mushroom cultivation, media bagging, sterilizing, spawning, incubation, and substrate harvesting were conducted. The study also observed in mycelium development, spawn run, pin head formation, and yield. The results shows that the addition of BS into the RS substrate has accelerated the first pinhead formation compared to 100% RS and 100% RS. Substrate with 25% RS + 75% BS mixture has the highest yield in terms of mean stipe length, which was 17.76 cm. This optimum composition recorded the average fresh weight of 123.28 g and average number of fruiting bodies of roughly 5.53. With a stipe length of 6.14 cm, the BS100% substrates produced the lowest total yield (89.04 g). As a result, it has been demonstrated that the substrates mixed with BS generated more edible mushrooms in terms of number and quality. Therefore, the substrate with combination of BS and RS demonstrated a high potential as an alternate grown media for the development of oyster mushroom. The results of this study could be advantageous to the mushroom and bamboo industries.